DAMPAK PENERAPAN SISTEM ENTERPRISE RESOURCE PLANNING (ERP) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ramadhanti, Seli; Saad, Bani (Journal of Accounting, Management and Islamic Economics, 2024)
This research aims to identify and analyse differences in financial performance seen from the return on assets (ROA), current ratio (CR), and debt to equity ratio (DER) before and after the implementation of enterprise resource planning (ERP). This research is a quantitative research, in which the data was obtained from the annual financial statements contained on the company's official website, the official website of the Indonesia Stock Exchange (IDX), the official website of idn financials and the official website of the The Indonesia Capital Market Institute (TICMI). The sample used in this research was determined using purposive sampling, so that there were a sample of 30 manufacturing companies listed on the IDX that had implemented the ERP system in the 2003-2017 period. Data were analyzed by comparing various ratios over the three years before and the three years after ERP system implemantation. The results of this research indicate that there is no significant difference in financial performance seen from the return on assets (ROA) and current ratio (CR), but there is significant different from debt to equity ratio (DER) between before and after ERP implementation.